PHYSICAL EDUCATION AND THE ENVIRONMENT: AN INEVITABLE RELATION (Fiep Bulletin - online, 2014)
The  purpose of this search was to study the relation between Physical Education (PE) and the  Environment. We understand that PE will have to contribute to the comprehension of this important theme, being open to new speeches and practices, searching for new ways for the profession and giving answers to the challenges that come all the time.The environmental issue became universal and has synthesized great current challenges: it has incorporated and requested help and actions from several areas of knowledge. It is consensual the necessity to surpass the monodisciplinary  paradigms. It is extremely important that the PE professionals recognize as their competence to help others understand this fact, and the process of humanity evolution.
Keywords: Physical Education; environment